Evaluation of effectiveness of psychoactive substance abuse prevention program “My Way”: transformations in the 9th-12th grades pupils’ perceptions about psychoactive substance use - Valantiejienė, Sandra; Saveljeva, Regina (Business, Management and Economics Engineering, 2019)
Purpose – The purpose of the article is to describe the transformations in the perceptions of the consequences of the use of psychoactive substances between 9-12’th grades pupils in the context of the implementation of the psychoactive substances abuse prevention program “My Way”.Research methodology – the authors performed a quasi-experiment and according to the methodological requirements related to the use of such scientific method in the educology studies, used an unequal control group and the primary/initial (pre-test) as well as final (post-test) measurements to achieve the aim of the research/article.Findings – the data of the quasi-experiment research showed that as the whole after intervention the pupil’s perceptions about the use of psychoactive substances in the experimental group has changed; the pupils who were assigned to the control group assessed the effects of the use of psychoactive substances better than those who were assigned to the control group.Research limitations – during the implementation of the program and the experiment, the activities related to the quasi-experiment were held only by social pedagogues in certain selected schools and classes (considering various factors such as the behaviour of children or their attributability to the families at social risk). Accordingly, in the next similar studies, children can be sampled evenly, without differentiating them based on their behavioural problems.Practical implications – the results of the research could be used in practice in the following ways: (i) by motivating the schools of general education in the Republic of Lithuania to choose prevention programs as the purposeful and meaningful instrument to develop healthy life skills; (ii) to develop and expand the range of new prevention programs based on the experience of the program “My Way” which is presented and evaluated in this article.Originality/Value – there are no similar previous educological and other educational science studies (in Lithuania) how the pupils’ attitudes change during the pre-planned and systematically implemented preventive activities in general education schools; the article presents and outlines the experience and practice of the first such Lithuanian program for the prevention of psychoactive substance abuse (“My Way”).